Conceptualising social justice – what constitutes pedagogies for social justice in HPE across different contexts?. Issue 2 (4th May 2019) - Schenker, Katarina; Linnér, Susanne; Smith, Wayne; Gerdin, Göran; Mordal Moen, Kjersti; Philpot, Rod; Larsson, Lena; Legge, Maureen; Westlie, Knut
ABSTRACT: The paper explores the concept of social justice in Health and Physical Education (HPE) as constituted and addressed across three different countries – Sweden, Norway and New Zealand – and how HPE teaching practices for social justice may be understood from regulative, normative and cultural/cognitive perspectives. Although much has been written about social justice in the field of HPE over the last three decades, there is little research that has examined how teachers operationalise teaching for social justice. Drawing on the experiences and insights gained from an international collaboration project, that sought to address this knowledge gap, this paper examines what constitutes pedagogies for social justice in HPE across different contexts. The aim of this paper is to discuss: (i) our conceptualisation of social justice; and (ii) how this can be understood in relation to HPE practice across different contexts. We conclude that what is regarded as important content for the teaching of social justice varies from one context to another although there are also similar approaches. Additionally, there is much to learn by seeing 'it', that is, the nature of social justice and how this is played out in school HPE – from the 'others' perspectives'.